2007
DOI: 10.26719/2007.13.5.1216
|View full text |Cite
|
Sign up to set email alerts
|

Osler-Weber-Rendu disease: report of 3 cases in a family

Abstract: Osler-Weber-Rendu disease, also referred to as hereditary haemorrhagic telangiectasia, is a genetic disease, an autosomal dominant disorder characterized by telangiectasias and aneurysms with primary involvement of the mucosa. The reported prevalence of this disease is 1-2 cases per 100 000 population [1]. The disease most commonly occurs in white patients, but has also been described in patients of Asian, African and Arab descent, and occurs with equal frequency and severity in both sexes. The syndrome most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Shamsadini et al also found similar results in that they studied patients with chronic renal failure who had had a history of hemodialysis for more than one year. In addition to BUN levels which were found to decrease significantly after hemodialysis, serum creatinine levels also declined considerably after hemodialysis (p<0.05) 40 . Serum creatinine levels (serum creatinine, SC) in this study were found to have significantly reduced with levels before hemodialysis of 12.76 ± 3.78 mg/dL and decreased to 4.56 ± 1.68 mg/dL after hemodialysis (p <0.001).…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 87%
“…Shamsadini et al also found similar results in that they studied patients with chronic renal failure who had had a history of hemodialysis for more than one year. In addition to BUN levels which were found to decrease significantly after hemodialysis, serum creatinine levels also declined considerably after hemodialysis (p<0.05) 40 . Serum creatinine levels (serum creatinine, SC) in this study were found to have significantly reduced with levels before hemodialysis of 12.76 ± 3.78 mg/dL and decreased to 4.56 ± 1.68 mg/dL after hemodialysis (p <0.001).…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 87%